The Fundamental Expressions of Fear in Sofia Samatar's The Huntress - Hariyono; Wijaya, Silvia Marta; Wijaya, Kusuma; Pasopati, Rommel Utungga; Kartiningsih, Rindrah (Universitas Brawijaya, 2024)
This article underlines the expressions of fear in Sofia Samatar’s flash fiction entitled The Huntress. The fear felt by the townspeople was thick, the darkness and silence merged. The moon was shining, everyone had their windows shut tight, and a brave man had come to visit the town. The silence is in line with a frightening situation in the story of The Huntress by Sofia Samatar. This paper would like to answer the question of how may fear be accentuated in Sofia's Samatar's The Huntress? Through qualitative method with cultural studies approach in the theory of myth by Claude Levi-Strauss, this paper locates expressions of fear, darkness, and courage in a story of The Huntress by Sofia Samatar. Darkness expresses the threat and disgrace experienced by the townspeople, the hunters are like a feared tenor lion, but then comes a young stranger who calls for courage in the townspeople. The fear of the townspeople is such a socio-cultural myth that has been embraced by them for a long time. In conclusion, the story shows how a young stranger tries to dispel the fear that gnaws at the townspeople's souls, convincing them that hunters are not dangerous